Comparative Study of Issues Affecting Erp Implementation In Large Scale and Small Medium Scale Enterprises In India: Exploring Issues in ERP Implementation for Indian SMEs vs Large Enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Issues which are considered more important for largescale enterprises may not be of equal importance for a small and medium scaleenterprise and hence replicating the implementation experience which holds forlarge organizations will not a wise approach on the part of the implementationvendors targeting small scale enterprises. This paper attempts to highlightthose specific issues where a different approach needs to be adopted. Paretoanalysis has been applied to identify the issues for Indian SMEs and Largescale enterprises as available from the published literature. Also by doingcomparative analysis between the identified issues for Indian large enterprisesand SMEs four issues are proved to be crucial for SMEs in India but not forlarge enterprises such as proper system implementation strategy, clearlydefined scope of implementation procedure, proper project planning and minimalcustomization of the system selected for implementation, because of somelimitations faced by the Indian SMEs compared to large enterprises.